2012
DOI: 10.1016/j.seizure.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Granule cell dispersion is associated with memory impairment in right mesial temporal lobe epilepsy

Abstract: GCD may be related to memory impairment in right MTLE-MTS patients. However, the role of GCD in memory function is not precisely defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…The dense associative network and the laminar organization, in which cell bodies are tightly packed, are evident also in insect's mushroom bodies (Menzel and Giurfa, ; Hochner, ) and mammalian's hippocampus (Neves et al., ; Bartsch and Wulff, ).…”
Section: Discussionmentioning
confidence: 99%
“…The dense associative network and the laminar organization, in which cell bodies are tightly packed, are evident also in insect's mushroom bodies (Menzel and Giurfa, ; Hochner, ) and mammalian's hippocampus (Neves et al., ; Bartsch and Wulff, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two other studies also found no relationship between neuronal cell counts of the right hippocampus and other nonverbal memory measures (Rausch and Babb, ; Baxendale et al, ). However, there may be other relevant neuropathological markers beyond neuronal cell loss: A recent study showed that the presence of granule cell dispersion was associated with worse presurgical nonverbal memory performance in right (vs. left) mTLE (Neves et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GCD is variably described in ILAE HS types 1, 2, and 3 (Blumcke et al., ; Thom et al., ), and may also occur in patients without hippocampal neuronal cell loss (Blumcke et al., ). Evidence currently suggests GCD as result of Reelin deficiency in the DG (Haas et al., ; Haas & Frotscher, ; Kobow et al., ), and that the presence of GCD is associated with greater cell loss in the hilus, an older age at epilepsy surgery, and longer epilepsy duration (Blumcke et al., ; Neves et al., ). The involvement of granule cells in the mechanisms of plasticity and memory formation also suggests that depletion of granule cells, in particular within the internal limb (Altman & Bayer, ), could be related to memory impairment in patients with TLE (Pauli et al., ; Blumcke et al., ; Coras et al., ; Neves et al., ).…”
Section: The Ilae Classification Of Hs In Patients With Tlementioning
confidence: 99%